The EFFECT OF UNDERSTANDING TAX REGULATIONS, APPLICATION OF TAXATION E-SYSTEMS, AND THE ROLE OF ACCOUNT REPRESENTATIVES ON TAXPAYER COMPLIANCE WITH PERSONAL PERSON - Kadek Wulandari Laksmi P; I G. N.O. Ariwangsa; Ni Wayan Lasmi; Ida Ayu Ratih Dharmayanti Tatwa (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
T The aims of this study was to determine the impact of understanding tax regulations, the application of the taxation e-system, and the role of account representatives on individual taxpayer compliance. The population in this study is the taxpayer of KPP Pratama Denpasar Timur. Determination of the number of samples using the Slovin formula with random sampling in order to obtain as many as 100 samples. Multiple linear regression analysis was used to analyze the data in this study. The results showed that the understanding of tax regulations, the application of the taxation e-system and account representatives had a positive and significant effect on the compliance of taxpayers in carrying out their tax obligations. This shows that the better the understanding of taxpayers on tax regulations, the implementation of the e-system of taxation and account representative services will be able to increase the compliance of taxpayers in carrying out their tax obligations at KPP Pratama Denpasar Timur